Parametric Equations of General Helices in the Sol Space Sol3 - Turhan, Essin; Korpinar, Talat (Soc Paranaense Matematica, 2013)
In this paper, we study general helices in the Sol(3). We characterize the general helices in terms of their curvature and torsion. Finally, we find out their explicit parametric equations in the Sol(3).
Keywords: General helix; Sol Space; Curvature; Torsion